Association between rs12252 and influenza susceptibility and severity: an updated meta-analysis. (13th November 2018) - Chen, T.; Xiao, M.; Yang, J.; Chen, Y. K.; Bai, T.; Tang, X. J.; Shu, Y. L.
Abstract: In several lately published studies, the association between single-nucleotide polymorphism (SNP, rs12252) of IFITM3 and the risk of influenza is inconsistent. To further understand the association between the SNP of IFITM3 and the risk of influenza, we searched related studies in five databases including PubMed published earlier than 9 November 2017. Ten sets of data from nine studies were included and data were analysed by Revman 5.0 and Stata 12.0 in our updated meta-analysis, which represented 1365 patients and 5425 no-influenza controls from four different ethnicities. Here strong association between rs12252 and influenza was found in all four genetic models. The significant differences in the allelic model (C vs. T: odds ratio (OR) = 1.35, 95% confidence interval (CI) (1.03–1.79), P = 0.03) and homozygote model (CC vs. TT: OR = 10.63, 95% CI (3.39–33.33), P < 0.00001) in the Caucasian subgroup were discovered, which is very novel and striking. Also novel discoveries were found in the allelic model (C vs. T: OR = 1.37, 95% CI (1.08–1.73), P = 0.009), dominant model (CC + CT vs. TT: OR = 1.48, 95% CI (1.08–2.02), P = 0.01) and homozygote model (CC vs. TT: OR = 2.84, 95% CI (1.36–5.92), P = 0.005) when we compared patients with mild influenza with healthy individuals. Our meta-analysis suggests that single-nucleotide T to C polymorphism of IFITM3 associated with increasingly risk of severe and mild influenza in both Asian and Caucasian populations.